Prevalence and survival of escaped European seabass Dicentrarchus labrax in Cyprus identified using genetic markers - Brown, Catherine J.; Miltiadou, Despoina; Tsigenopoulos, Costas S. (My University, 2015)
The escape of European seabass Dicentrarchus labrax (L.) from fish farms is considered to be a widespread problem in the Mediterranean area, where this species is produced in large quantities in offshore cages. Whilst estimates of the number of escaped seabass in the wild have been made previously, the actual distribution, long-term survival and the potential effects on native populations remain largely unknown. This study characterises the genetic profiles of all contemporary and some historic aquaculture sources of European seabass in Cyprus and uses these profiles to identify escaped fish in seabass collected from the wild around the island. Significant differences in the microsatellite and mitochondrial DNA marker profiles were found between farmed and wild fish. The number of escapees identified was 15% of the total number of wild-caught fish sampled. However, escapees were not equally distributed; at one location ~70% of wild-caught fish were escapees while in other areas escapees only accounted for up to 4%. Escapees were present in all size classes of fish, but the majority were of commercial size (300-500 g) typical of seabass farmed in seacages. This indicates that they may have escaped recently and during normal aquaculture operations as no escape event was reported in the course of the study. Two large, egg-bearing females and some juvenile fish were also classified as escapees, which suggests that long-term survival and interbreeding with wild fish is possible in Cypriot waters.
Keywords: Aquaculture impacts; Genetic identification; Interbreeding; Introgression; Microsatellites; Mitochondrial DNA